(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Mr. Breals Shawarma is a fast-food restaurant. The company was founded on July 29th of 2021, during the pandemic, which allowed them to position the brand and increase sales. Mr. Breals Shawarma is a fast-food restaurant. The company was founded on July 29th, 2021, during the pandemic, which allowed them to position the brand and increase sales. The findings of the study revealed that the majority of the respondents are 16-25 years old, female unemployed, and availed of price discounts. The respondents evaluated Mr. Breals Shawarma's sales promotion as “Effective.” The overall result obtained a weighted mean of 3.05, interpreted as effective. As revealed, the problem encountered by the respondents is it has limited visibility and display. The results revealed the following recommendation: use a variety of discounts, including bundled discounts, customer loyalty discounts, volume discounts, and many others. Include means for acquiring the price reduction promotion, as well. Mr. Breals Shawarma should begin creating a website to promote their free shipping promotion in order to reach more people and attract more customers. Include detailed instructions on how to take advantage of the free shipping promotion on the website or on a social media post to avoid misleading claims about the deal. Mr. Breals Shawarma should boost its buy-one-get-one offers by giving additional products to customers, such as purchasing three get-one free drinks or other items, and so on, to improve its effectiveness and attract more clients. Mr. Breals Shawarma should start a sales campaign before and throughout the holiday to boost the impact of the promotion.